2015
DOI: 10.3892/ijo.2015.2845
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to leptin enhances the growth of prostate cancer cells

Abstract: Obesity correlates with an increased risk of developing prostate cancer (PCa) and leptin plays an important role in PCa progression. Since leptin is produced by adipocytes, the serum leptin level is higher in obese than in non-obese individuals. However, the effects of leptin remain controversial and unclear. The aim of the present study was to investigate the effect of leptin on PCa cell aggressiveness. Three human PCa cell lines (LNCaP, DU145 and PC-3) were treated with recombinant leptin for 28 days. Cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 41 publications
(26 reference statements)
0
38
0
3
Order By: Relevance
“…However, the effects of leptin remain controversial and unclear [28]. Long-term exposure of PC cells to leptin enhances their proliferation, migration and invasion, and leptin increases the leptin receptor expression and enhances prokinase B (Akt) phosphorylation constitutively, as postulated currently by Noda et al [29].…”
Section: Discussionmentioning
confidence: 97%
“…However, the effects of leptin remain controversial and unclear [28]. Long-term exposure of PC cells to leptin enhances their proliferation, migration and invasion, and leptin increases the leptin receptor expression and enhances prokinase B (Akt) phosphorylation constitutively, as postulated currently by Noda et al [29].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies demonstrated that the variants might elevate the serum leptin level through transcriptional level, and increase human body weight as well [39, 40]. Higher leptin level, in turn, contributed to cancer growth and development via stimulating inflammation, angiogenesis, proliferation and epithelial-mesenchymal transition [10, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…Several isoforms of the leptin receptor have been reported in human tissues including the prostate and testes [18,19]. In this study, no diagnosis or follow-up of prostate cancer was performed as Canacci et al [20], they studied the chemicals products in the male accessory glands and related them to the Gleason score [20].…”
Section: Discussionmentioning
confidence: 99%